Serological and molecular surveillance of West Nile virus in domesticated mammals of Peninsular Malaysia - Mohammed, Mohammed Nma; Yasmin, Abd Rahaman; Ramanoon, Siti Zubaidah; Noraniza, Mohd Adzahan; Ooi, Peck Toung; Ain-Najwa, Mohd Yuseri; Natasha, Jafar Ali; Nur-Fazila, Saulol Hamid; Arshad, Siti Suri; Mohammed, Hussni Omar (Frontiers Media, 2023)
West Nile virus is a mosquito-borne neurotropic pathogen with a wide host range that constitutes a significant risk to public and animal health. There is limited information on WNV infection in domesticated mammals in Malaysia; however, current reports indicate infections in birds, macaques, bats and pigs from Malaysia. In this study, 203 serum samples from cattle, goats, and horses were tested for the presence of anti-WNV IgG using a competitive enzyme-linked immunosorbent assay (c-ELISA). Additionally, using one-step RT-PCR, nasopharyngeal swabs were analyzed for WNV RNA from all 203 animals in this study. The WNV seroprevalence was 32.53% (27/83) at 95% CI (0.2342–0.4319) in cattle, 48.27% (14/29) at 95% CI (0.3139–0.6557) in goats and 53.84% (49/91) at 95% CI (0.4366–0.6373) in horses. Cross-reactive JEV antibodies were detected in two cattle and 34 horses. None of the cattle or goats tested positive for WNV RT-PCR. Seven horses were positive for WNV RT-PCR, a molecular prevalence of 7.69% (7/91) at 95% CI (0.0353–0.1528). This is the first reported detection of WNV in domesticated mammals of Malaysia, a significant addition to the growing evidence that WNV is being transmitted from vectors to susceptible hosts in Malaysia.